MR of the caudal regression syndrome: embryologic implications. - Nievelstein, R A; Valk, J; Smit, L M; Vermeij-Keers, C (American Journal of Neuroradiology, 1994)
PURPOSE To evaluate the spectrum of developmental anomalies observed in patients with the caudal regression syndrome and relate them to the pathogenesis of this syndrome. METHODS Nineteen children with caudal regression were investigated with MR. RESULTS The level of vertebral agenesis varied from T-11 to S-5. In 9 of the 19 children the characteristic high-ending wedge-shaped cord terminus was observed. A separation of the anterior and posterior spinal roots of the cauda equina was observed in 9 patients. Four patients had a tethered spinal cord, in 1 in combination with a wedge-shaped cord terminus. CONCLUSIONS The pathogenesis of the caudal regression syndrome can be divided into two kinds: there is usually a disturbance of the primary neurulation process; in other cases there is a derailment of the process of degeneration and differentiation of an initially normally developed primary and secondary neural tube. MR aids understanding of the morphology and pathogenesis of congenital malformations involved (including the associated anomalies of the genitourinary and gastrointestinal systems), but other studies are still necessary to determine the exact mechanism of this syndrome.